Support the girls [videorecording (DVD)] - Bujalski, Andrew; Gelula, Dylan, 1994-; Hall, Regina; Richardson, Haley Lu (Magnolia Home Entertainment, 2018)
Lisa is the last person some would expect to find in a highway-side 'sports bar with curves,' but as general manager at Double Whammies, she has come to love the place and its customers. An incurable den mother, she nurtures and protects her girls fiercely, but over the course of one trying day, her optimism is battered from every direction. Double Whammies sells a big, weird American fantasy, but what happens when reality pokes a bunch of holes in it?